Teaching Speaking Skills in English Classes at MTs Ma'ruf Wuluhan Jember - Moch. Imam Machfudi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2006)
The declining quality of speaking skills among Indonesian junior high school students remains a persistent issue in English as a Foreign Language (EFL) contexts. This study addresses the gap between curriculum expectations and students’ actual oral performance by examining how speaking instruction is integrated with other language skills. The research aims to describe the techniques and media used to teach speaking at MTs Ma’arif Wuluhan Jember. A qualitative approach was employed, using classroom observation, interviews, and documentation across three grade levels, with data analyzed using Miles and Huberman’s interactive model. The findings show that teachers integrate speaking into reading, listening, and writing activities through techniques such as reading aloud, repetition drills, question-and-answer, dialogue practice, storytelling, group discussion, role-play, and picture description. Media used include real objects, flashcards, tape recorders, and VCD players. The study concludes that integrative teaching, supported by appropriate media, enhances speaking effectiveness. Recommendations include ongoing teacher training and curriculum alignment to foster consistent oral practice. Menurunnya kualitas keterampilan berbicara bahasa Inggris pada siswa SMP/MTs di Indonesia masih menjadi isu krusial dalam pembelajaran bahasa Inggris sebagai bahasa asing. Penelitian ini menjawab kesenjangan antara tuntutan kurikulum dan kemampuan berbicara siswa dengan mengeksplorasi integrasi pembelajaran berbicara dengan keterampilan lain. Tujuannya mendeskripsikan teknik dan media pengajaran berbicara di MTs Ma’arif Wuluhan Jember. Metode kualitatif digunakan melalui observasi kelas, wawancara, dan dokumentasi pada tiga tingkatan kelas, dengan analisis data model Miles dan Huberman. Hasil penelitian menunjukkan guru mengintegrasikan keterampilan berbicara ke dalam membaca, menyimak, dan menulis melalui teknik membaca nyaring, drill repetisi, tanya-jawab, praktik dialog, bercerita, diskusi kelompok, bermain peran, dan deskripsi gambar. Media yang digunakan antara lain benda nyata, kartu bergambar, tape recorder, dan VCD player. Kesimpulannya, pengajaran terintegrasi dengan media efektif meningkatkan kemampuan berbicara. Rekomendasi mencakup pelatihan guru berkelanjutan dan penyesuaian kurikulum untuk praktik lisan yang konsisten.